THE STUDY OF RESISTANCE TO MOVEMENT OF AUTONOMOUS RAILWAY CARRIAGE - Babaiev, O. M.; Bodnia, M. V.; Harkavi, M . Ya. (Science and Transport Progress, 2006)
The article provides theoretical and experimental determination of the values of specific resistance to movement, which have been compared with the dependencies, used by the railways ofCIS,UKandPoland.